Utility of Hyaluronidase in Combination with Triamcinolone Acetonide and 5-Fluorouracil in Treatment of Hypertrophic Scars and Keloids: A Comparative Study - Divya Bhangdiya; Rachita Dhurat; Richa Sharma; Bhavika Shah; Geeta Shinde (Wolters Kluwer Medknow Publications, 2024)
Background: Keloids and hypertrophic scars are a commonly encountered problem in dermatology. There are many treatment modalities available with variable efficacy and recurrences. This study highlights the use of hyaluronidase with triamcinolone acetonide (TAC) and 5-fluorouracil (5-FU). Purpose: To assess the utility of hyaluronidase in combination with TAC and 5-FU in treatment of hypertrophic scars and keloids. Methods: In this study a combination of hyaluronidase along with TAC and 5-FU was given in one part and a combination of TAC and 5-FU was given in another half of same hypertrophic scar/keloid keeping 1cm gap in between the two untreated at 4 weekly interval for 24 weeks. Results were assessed by measuring height, volume of lesion and their percentage decrease. Also, pliability, vascularity, pigmentation of lesion and Vancouver scar assessment scale score were assessed. Side effects like ulceration, surrounding skin atrophy and telangiectasias were noted. Results: There was a reduction in all the parameters in both the treatment segments. Faster improvement in height, volume, pliability, vascularity, pigmentation, and Vancouver scar assessment scale score was noted with combination of hyaluronidase, TAC, and 5-FU compared to TAC and 5-FU alone. Side effect profile of ulceration, surrounding skin atrophy and telangiectasias was comparable in both the segments. Conclusion: Combination of hyaluronidase along with TAC and 5-FU offered a better outcome and faster response when compared to combination of TAC and 5-FU.